Having access to a cell phone increases women’s empowerment in rural Bangladesh. - Sarna, Sabrina (Université d'Ottawa | University of Ottawa, 2021)
This paper investigates the effect of access to cell phone on one dimension of women's empowerment, women's involvement in group activities in a developing country, Bangladesh. Bangladesh experiences a reduction in gender gap reflected in its improved ranking in Global Gender Gap ranking from 82 in 2010 to 64 in 2015. Simultaneously, coverage of access to cell phone has grown from 46% in 2010 to 84% in 2015. This provides an ideal setting to test whether access to cell phone impacts women's empowerment. Recent empirical literature (e.g., Rotondi et al. 2020, Hossain and Samad (2021)) does provide some evidence. The paper builds upon that literature by using the Bangladesh Integrated Household Surveys, a panel dataset conducted on a representative sample of 6,500 households in 2012 and 2015. This research improves on prior research by using the number of cell towers in a sub-district to instrument the effect of cell phone on women's empowerment. The instrumental variable approach is required as Women's empowerment, and access to cell phone are endogenous: it is possible that empowered women have a greater probability of having access to a cell phone. Hence, the observed positive relationship could be because of this reverse causation. I find that women having access to a cell phone increases woman's participation in group activities. This result is further robust when using alternative specifications. The effect of access to a cell phone on women's leadership role in group activities is not statistically significant.